Amorphous–amorphous phase separation in hydrophobically-modified starch–sucrose blends I. Phase behavior and thermodynamic characterization. (July 2016) - Tedeschi, Concetta; Leuenberger, Bruno; Ubbink, Job
Abstract: The glass transition of amorphous powders consisting of blends of octenyl-succinic anhydride (OSA) modified starch, and sucrose was studied as a function of blend composition and water content. Polarized light microscopy, differential scanning calorimetry (DSC) and water vapor sorption analysis were performed on four blends varying in their modified starch to sucrose ratio. The thermograms of the blends exhibit either a single glass transition event, characterized by a quite broad temperature range, or two glass transitions. This hints at a limited degree of phase separation into two amorphous phases within the blend matrix, most likely at the microscale. The results from dynamic water vapor sorption studies indicate that, in the phase-separated blends, the sucrose-rich phase constitutes the dispersed phase, while the continuous phase is formed by the phase rich in OSA starch. Our findings open up new ways to engineer glass encapsulation systems with composite structure, which can provide for a high level of protection of encapsulated bioactive compounds as well as defined release properties. Graphical abstract: Highlights: Phase separation is observed in amorphous blends of OSA starch and sucrose. The degree of phase separation depends on the blending ratio. The glass transition temperatures of the two phases are substantially different. The findings open new routes towards glass encapsulation systems for bioactives. The systems combine glassy-state barrier properties and enhanced aw stability.